Pengembangan Desain Miniatur Aktivitas Produksi Tempe Sebagai Buah Tangan Unggulan Kampung Industri Tempe Sanan - Ginanjar Atma Wijaya; Annisa Ayu Salsabila; Eka Putri Surya; Alby Aruna; Abdul Rahman Prasetyo; Adinda Marcelliantika (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The development of miniature design of tempe production activities as a flagship souvenir for Sanan Tempe Industry Village aims to enhance tourism appeal and local economic value. This program integrates cultural elements and tempe production processes into educational and aesthetic miniatures. Methods include design research, prototype creation, technical training for local craftsmen, and product evaluation through tourist feedback. Results show a significant increase in tourist interest and satisfaction with tempe miniatures. The implementation of this program is expected to support local cultural promotion and strengthen the economy of Sanan Tempe Industry Village.